2023
DOI: 10.3390/ijerph20010859
|View full text |Cite
|
Sign up to set email alerts
|

Teachers during the COVID-19 Era: The Mediation Role Played by Mentalizing Ability on the Relationship between Depressive Symptoms, Anxious Trait, and Job Burnout

Abstract: Background: The COVID-19 outbreak caused severe changes in school activities over the past two years. Teachers underwent a re-planning of their teaching approaches, shifting from face-to-face teaching formats to remote ones. These challenges resulted in high levels of burnout. The identification of risk/protective factors contributing to burnout is crucial in order to inform intervention programs. Thus, we hypothesized a mediation role of teachers’ mentalizing ability (processing of emotions, a component of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
0
6
0
1
Order By: Relevance
“…The effect of perceived stress on burnout is amplified in difficult and challenging situations, as emerged world-wide during the COVID-19 pandemic (Lizana et al, 2021;Pellerone, 2021;Vargas Rubilar and Oros, 2021;Levante et al, 2023). In a recent study, Geraci et al (2023) found that the pandemic emergency did indeed increase the risk of teachers' burnout and negatively impacted their level of work engagement, which is a persistent, positive and satisfying work-related mental state, characterized by vigor, absorption and dedication to work activities (Schaufeli et al, 2002).…”
Section: Perceived Stress Burnout and Work Engagement In The Teaching...mentioning
confidence: 99%
“…The effect of perceived stress on burnout is amplified in difficult and challenging situations, as emerged world-wide during the COVID-19 pandemic (Lizana et al, 2021;Pellerone, 2021;Vargas Rubilar and Oros, 2021;Levante et al, 2023). In a recent study, Geraci et al (2023) found that the pandemic emergency did indeed increase the risk of teachers' burnout and negatively impacted their level of work engagement, which is a persistent, positive and satisfying work-related mental state, characterized by vigor, absorption and dedication to work activities (Schaufeli et al, 2002).…”
Section: Perceived Stress Burnout and Work Engagement In The Teaching...mentioning
confidence: 99%
“…Investigaciones desarrolladas en el profesorado, han evidenciado la sobrecarga laboral manifestada en niveles altos de ansiedad, depresión y estrés (Levante et al, 2023;Mondragon et al, 2023). Lo anterior dificulta la calidad de desempeño y del trabajo docente y consecuentemente en los procesos de enseñanza y aprendizaje del estudiantado, dada la reciprocidad en la relación entre profesor-estudiante .…”
Section: Programa Psicoeducativo Aplicado En El Profesorado Como Meca...unclassified
“…Although these restrictive measures were effective in containing the spread of the infection [ [93] , [94] , [95] , [96] ], they negatively impacted the mental health of the general population [ [97] , [98] , [99] , [100] ]. People showed high levels of depressive symptoms, anxiety, concern, and psychological distress [ [101] , [102] , [103] , [104] , [105] ]. In addition, lockdowns led people to change their behaviour and routines, also in terms of physical activity, eating habits, sunlight exposure, and social interactions [ 97 , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] ].…”
Section: Introductionmentioning
confidence: 99%